A Case Report on Stavudine Induced Lipodystrophy - Gunturu, Lakshmi Narasimha; Pamayyagari, Kalpana; Dornadula, Girirajasekhar (Journal of Pharmacy Practice and Community Medicine)
Drug induced adverse drug reactions are more common in long term therapy particularly in immune compromised patients. Some of the drugs causes Redistribution of body fat (Lipodystrophy) in Human Immunodeficiency Virus (HIV) infected patients and loss of body fat (Lipoatrophy). Stavudine is the one of the first line regimens drugs used for HIV infection belongs to the category of Nucleoside reverse transcriptase enzyme inhibitor (NRTIs). In the present case, we have reported the stavudine induced severe Lipodystrophy (Lipoma). A patient visited the hospital with the symptoms of lump on back of neck as, she received Stavudine fixed dose combination (SLN) as a drug for her diagnosis of HIV for past seven years. After clear examination Lipodystrophy (Lipoma) was confirmed and suspected with the cause due to stavudine fixed dose regimen. The drug was stopped and the patient was opted to surgery for permanent cure. The patient was recovered from her condition and other antiretroviral drugs were recommended for her treatment.
Keywords: Antiretroviral therapy; Adverse drug reaction; Lipodystrophy; HIV; Lipoatrophy.